1995
DOI: 10.1002/1097-0142(19950615)75:12<2946::aid-cncr2820751223>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic variation in cancer survival in the Southeastern Netherlands, 1980-1989

Abstract: Background. The survival rates of patients with cancer by socioeconomic status (SES) has never been investigated in the Netherlands, a country characterized by good general access to health care services. The association between socioeconomic status and survival from cancer of the lung (n = 4591), breast (n = 3928), colorectum (n = 3558), prostate (n = 1484), and stomach (n = 1455) was studied, and the impact of some prognostic factors (stage at diagnosis, histologic type, and treatment) on this association wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 17 publications
3
44
2
Order By: Relevance
“…3,[32][33][34] Other studies in European countries reported a cancer overmortality of 25 to 50% among breast cancer patients of low SES. 3,10,[35][36][37] The number of cancer deaths in Europe that could potentially be avoided by eliminating social variation in cancer survival appeared particularly important for breast cancer. 38 Even though Switzerland has one of the best equipped healthcare systems in Europe, this study shows that breast cancer patients of low SES have a 2.4-fold increased risk of dying of breast cancer compared with the risk for breast cancer patients of high SES.…”
Section: Discussionmentioning
confidence: 99%
“…3,[32][33][34] Other studies in European countries reported a cancer overmortality of 25 to 50% among breast cancer patients of low SES. 3,10,[35][36][37] The number of cancer deaths in Europe that could potentially be avoided by eliminating social variation in cancer survival appeared particularly important for breast cancer. 38 Even though Switzerland has one of the best equipped healthcare systems in Europe, this study shows that breast cancer patients of low SES have a 2.4-fold increased risk of dying of breast cancer compared with the risk for breast cancer patients of high SES.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic differences in cancer survival have been observed in many countries (Kogevinas and Porta, 1997;Ward et al, 2004), including the Netherlands (Schrijvers et al, 1995a), Canada (Mackillop et al, 1997), England and Wales (Coleman et al, 1999), Scotland (Scottish Cancer Intelligence Unit, 2000) and the United States (Singh et al, 2003). In England and Wales, recent improvements in survival have been more marked in affluent groups, actually widening the socioeconomic inequality in survival (Coleman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic gradients in colorectal cancer survival may be explained by differences in treatment (Faivre-Finn et al, 2002;Guyot et al, 2005;Yu et al, 2005), stage at diagnosis (Singh et al, 2003) or comorbidity (Schrijvers et al, 1995a;Wrigley et al, 2005), although such differences are not consistent (Ionescu et al, 1998;Brewster et al, 2001;Wrigley et al, 2005). In Scotland, deprived and affluent patients diagnosed during 1991 -1994 had similar curative resection rates, but survival was lower among deprived patients, even after adjusting for stage at diagnosis and type of operation (Hole and McArdle, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We have no data on non clinical prognostic factors which could be important such as socio-economic status. Lung cancer patients living in better socio-economic areas are known to have more favourable survival compared to patients living in the lower socio-economic areas of the southeastern part of the Netherlands (Schrijvers et al, 1995). This observation was confirmed by the Cancer and Leukaemia Group B, which reported that small cell lung cancer patients with a lower annual income and lower educational level had a shorter survival than those with higher income or education Experimental Therapeutics No significant difference P50.13 for any of the parameters for the off and on trial groups.…”
Section: Discussionmentioning
confidence: 99%